Peran Pos Bantuan Hukum Dalam Melayani Keadilan Masyarakat - ismayana ismayana (Hukum Responsif, 2015)
Legal Aid as an important part in providing access to justice become a very popular topic. This is not only a topic and a national issue but also become a hot issue in the world today ini.Undang of the Republic of Indonesia Number 16 of 2011 on Legal Aid confirms that the State guarantees the constitutional right of every person to gain recognition, security, protection and legal certainty fair and equal treatment before the law as a means of human rights protection. So that people who come to the trial already have and prepare the necessary documents, so that the process can be more smoothly litigants so that the principle is simple, fast and low cost can be met. Keywords: legal aid, constitutional rights, Principles of Law.